Applying Wasaṭīyah within the Malaysian Religio-Political Context - Ahmad El-Muhammady (American Journal of Islam and Society, 2015)
There is a resurgence of interest in the wasaṭīyah (moderation) approach among contemporary Muslim academics and policymakers, particularly with regards to its application and utility in resolving social challenges. This renewed interest apparently intensified especially due to Samuel Huntington’s 1993 “clash of civilizations” thesis in the aftermath of 9/111 and the emergence of extremism and liberal thinking in the Muslim world.2 This short essay argues that the need for wasaṭīyah in the present-day context is not due to that factor alone; rather, it is a response to the pervasive extremism manifesting itself in various forms, either in the practice of politics, economics, culture, religion, and others. Economic extremism produced exploitation, market manipulation, inequality, and poverty in many countries. In the realm of politics, extremism appears in the form of global domination, authoritarianism, and even democratization projects that ignore the country’s socio-political contexts. Such an effort is meaningless to the locals and, at worst, might jeopardize the democratization project itself. In addition, the rise of modernity and postmodernity has produced unintended consequences. Modern society tends to engage in the endless pursuit of materialism and conspicuous consumerism, both of which devalue spirituality and the religious life. Modern people, therefore, are intellectually sophisticated but suffer from a spiritual-ethical vacuum due to their excessive pursuit of material gain. The “reign of quantity,” as Rene Guénon argued, not only rules supreme in the economic and business domains, but also permeates institutions of higher learning. Eventually liberal education does produce ...